2016
DOI: 10.1038/srep24968
|View full text |Cite
|
Sign up to set email alerts
|

Smad6 determines BMP-regulated invasive behaviour of breast cancer cells in a zebrafish xenograft model

Abstract: The transforming growth factor-β (TGF-β) family is known to play critical roles in cancer progression. While the dual role of TGF-β is well described, the function of bone morphogenetic proteins (BMPs) is unclear. In this study, we established the involvement of Smad6, a BMP-specific inhibitory Smad, in breast cancer cell invasion. We show that stable overexpression of Smad6 in breast cancer MCF10A M2 cells inhibits BMP signalling, thereby mitigating BMP6-induced suppression of mesenchymal marker expression. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Alterations that cause persistent high levels of Smad7 blunt TGF-b signaling and have been described in endometrial carcinomas and thyroid follicular tumors (Cerutti et al 2003;Dowdy et al 2005). Similarly, increased Smad6 expression also attenuates TGF-b family signaling, preventing its tumor-suppression function in pancreatic or breast cancer (Kleeff et al 1999;de Boeck et al 2016). As reported above for Smad4 depletion in genetic models, Smad7 overexpression in immune cells has been associated with chronic inflammation in the colonic mucosa.…”
Section: Signaling Mediatorsmentioning
confidence: 96%
“…Alterations that cause persistent high levels of Smad7 blunt TGF-b signaling and have been described in endometrial carcinomas and thyroid follicular tumors (Cerutti et al 2003;Dowdy et al 2005). Similarly, increased Smad6 expression also attenuates TGF-b family signaling, preventing its tumor-suppression function in pancreatic or breast cancer (Kleeff et al 1999;de Boeck et al 2016). As reported above for Smad4 depletion in genetic models, Smad7 overexpression in immune cells has been associated with chronic inflammation in the colonic mucosa.…”
Section: Signaling Mediatorsmentioning
confidence: 96%
“…The extra-uterine development of hundreds of eggs also permits a greater number of studies in genetically identical organisms. Since the first reported xenotransplantation of human cells into zebrafish ( Lee et al , 2005), many laboratories have shown that zebrafish embryos are useful for the study of other facets of tumour biology including cancer-induced angiogenesis ( Haldi et al , 2006); cancer cell invasion and metastasis ( de Boeck et al , 2016; Marques et al , 2009); cancer stem cell growth ( Bansal et al , 2014; Chen et al , 2017); interaction of cancer cells with the host ( Feng & Martin, 2015); and drug screening ( Corkery et al , 2011; Gibert et al , 2013). Importantly, the development of human tumours and their response to chemotherapeutic treatment in zebrafish embryos is comparable to that observed in mouse xenograft assays ( Fior et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This includes the development of embryonic zebrafish xenograft models to study the pathogenesis of human cancers,41–43 including human breast cancers 44,45. Here, MDA‐MB‐231 breast cancer cells, stably expressing GFP, were microinjected into the circulation of 2‐day old zebrafish larvae via the duct of Cuvier and quickly accumulated (<1 h post injection [hpi]) within the caudal hematopoietic tissue (CHT) 46. One hour after injection of cancer cells, either fluorescently labeled E PEG ‐ or F PEG ‐liposomes (4 mol% PEG 5000 , 1 mol% DOPE‐LR probe) were injected (1 m m , 3 nL) into circulation via the posterior cardinal vein (PCV).…”
Section: Resultsmentioning
confidence: 99%